Insect Pest occurrence on Cultivated Amaranthus Spp in Benin City, Edo State, Nigeria - AE Ezeh; ABO Ogedegbe; SA Ogedegbe (Journal of Applied Sciences and Environmental Management)
Amaranthus is one of those rare plants whose leaves are eaten as vegetables and seeds as cereal.   Unfortunately, one of the major factors limiting the productivity of Amaranthus is the incidence of insect pests attack. The aim of this study was to determine the insect pest occurrence on cultivated Amaranths in Benin City, Nigeria. The experiment was conducted in the Agricultural farm of University of Benin, Edo State,  Nigeria. Three varieties of Amaranth were used for this experiment, namely, Amaranthus cruentus (white–seeded), Amaranthus hybridus (red–seeded) and Amaranthus hybridus (black–seeded). The experimental  design used was completely randomized design with three replicates, each replicate having nine plots. The result showed the diversity of insect pests associated with Amaranth. Insects found on Amaranth were  classified into seven (7) orders, namely Coleoptera, Lepidoptera, Diptera, Hemiptera, Orthoptera,  Hymenoptera and Mantodea; and eight (8) species. The species included Gasteroclisus rhomboidalis and  Hypolixus sp. (Coleoptera); Hymenia recurvalis and Psara sp. (Lepidoptera); Liriomyza sp. (Diptera); Cletus sp. and Aspavia armigera (Hemiptera) and Zonocerus variegates (Orthoptera). Majority of the pests are defoliators, except Cletus sp. and Aspavia armigera that attack grains. The result also revealed that the period of pest occurrence is associated with Amaranth age. Knowledge from this study can be employed by Amaranth growers to ensure proper management of these insect pests.